Teacher Empowerment in State Junior High Schools in Indonesia: Policies Review - In’am, Akhsanul; Hussin, Sufean (International Journal of Independent Research Studies, 2013)
The objective of this research is to delineate and analyse the policies on teacher empowerment in the context of decentralization of education implemented in Malang, Indonesia. In order to understand the chain of institutions and their authorities in applying the policies in six State Junior High Schools a qualitative approach was employed. The data on the implementation of the policies in the chosen schools and agencies are obtained through document analyses, observations and interviews involving 35 respondents consisting of parliament members, education councils, members and heads of school committee and teachers. The results of the research show that the institutions implementing the teacher empowerment, namely the local parliament, the department of education, education council, and school committee have not yet been able to do their functions and obligations maximum in accordance with the message in the reformation of education. Meanwhile status and self-confidence dimensions have not been able to give maximum satisfaction to them as teachers.